A Preliminary Study of the Suitability of Archival Bone Marrow and Peripheral Blood Smears for Diagnosis of CML Using FISH - Alice Charwudzi; Edeghonghon E. Olayemi; Ivy Ekem; Olufunmilayo Olopade; Mariann Coyle; Amma Anima Benneh; Emmanuel Alote Allotey (Advances in Hematology)
Background. FISH is a molecular cytogenetic technique enabling rapid detection of genetic abnormalities. Facilities that can run fresh/wet samples for molecular diagnosis and monitoring of neoplastic disorders are not readily available in Ghana and other neighbouring countries. This study aims to demonstrate that interphase FISH can successfully be applied to archival methanol-fixed bone marrow and peripheral blood smear slides transported to a more equipped facility for molecular diagnosis of CML. Methods. Interphase FISH was performed on 22 archival methanol-fixed marrow (BM) and 3 peripheral blood (PB) smear slides obtained at diagnosis. The BM smears included 20 CML and 2 CMML cases diagnosed by morphology; the 3 PB smears were from 3 of the CML patients at the time of diagnosis. Six cases had known BCR-ABL fusion results at diagnosis by RQ-PCR. Full blood count reports at diagnosis were also retrieved. Result. 19 (95%) of the CML marrow smears demonstrated the BCR-ABL translocation. There was a significant correlation between the BCR-ABL transcript detected at diagnosis by RQ-PCR and that retrospectively detected by FISH from the aged BM smears at diagnosis (r=0.870; P=0.035). Conclusion. Archival methanol-fixed marrow and peripheral blood smears can be used to detect the BCR-ABL transcript for CML diagnosis.